EVENT MICE FESTIVAL UMA LENGGE MARIA SEBAGAI UPAYA MENINGKATKAN KUNJUNGAN WISATA BUDAYA DI KECAMATAN WAWO KABUPATEN BIMA NTB - Devi Anggriani; Ni Wayan Mekarini (Universitas Triatma Mulya, 2023)
The aim of research entitled ‘Uma Lengge Maria Festival Event as event to invite more Visitor to Maria tourism Village di Wawo District Bima West Nusa Tenggara to describe the roles of the festival in increasing tourist coming to this object. This research use desciptive qualitative approach, that is systematically describe facts in a particular field or fenomena. Data collection methods were carried out by observation, interviews and documentation then analyzed in the stages of data collection, data reduction, data presentation and drawing conclusions. The informan of this research were selected based on the following characteristics: (1) were at the location when the event take place, (2) witnessed the progress of the event, (3) filled in the guest list, (4) are native people of Bima, (5) knew about the progress of the event, and (6) live near the festival location. The research results show that the Uma Lengge Maria Festival Event has main role in increasing cultural tourism with the MICE industry, especially in Bima where some traditional cultural values are shown and local product are displayed to public. It also improving the economy stage and tourism development in Bima